2010
DOI: 10.1128/aem.01321-10
|View full text |Cite
|
Sign up to set email alerts
|

Both Leaf Properties and Microbe-Microbe Interactions Influence Within-Species Variation in Bacterial Population Diversity and Structure in the Lettuce ( Lactuca Species) Phyllosphere

Abstract: Morphological and chemical differences between plant genera influence phyllosphere microbial populations, but the factors driving within-species variation in phyllosphere populations are poorly understood. Twenty-six lettuce accessions were used to investigate factors controlling within-species variation in phyllosphere bacterial populations. Morphological and physiochemical characteristics of the plants were compared, and bacterial community structure and diversity were investigated using terminal restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
156
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(170 citation statements)
references
References 55 publications
12
156
1
1
Order By: Relevance
“…In contrast, Xanthomonas was present in only 33 of 88 samples in a survey in California (14). Pantoea, which is a member of the Enterobacteriaceae family, is also found to be one of the major genera in other studies of the leafy-green phyllosphere (5,11,14). The genus Pantoea includes several species that are generally associated with plants as either epiphytes or pathogens, and some species can cause disease in humans (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Xanthomonas was present in only 33 of 88 samples in a survey in California (14). Pantoea, which is a member of the Enterobacteriaceae family, is also found to be one of the major genera in other studies of the leafy-green phyllosphere (5,11,14). The genus Pantoea includes several species that are generally associated with plants as either epiphytes or pathogens, and some species can cause disease in humans (38).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial communities associated with leafy greens have already been described by several culture-independent studies. "First-generation" molecular techniques have been used to describe variation in community structure in the context of leaf surface properties and microbial interactions (5), seasonal variation in the community structure (6), and monitoring of bacterial communities in the food chain (7). The introduction of culture-independent methods, in particular, microbial profiling using high-throughput sequencing to study microorganisms, has revealed more complexity and diversity of the phyllosphere microbiota and has dramatically changed the landscape of microbial ecology (5,(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent culture-independent community analyses have confirmed the apparent selectivity of leaf surfaces, finding that leaf surfaces harbor less diverse communities than other environments, such as the immediate subtending soil (3,4). Furthermore, plant species identity also appears to be a factor that can influence the composition of associated phyllosphere bacterial communities (5)(6)(7)(8)(9). While epiphytes are apparently distinct in their ability to grow and survive on leaves, their adaptations needed to thrive in this habitat remain largely unknown.…”
mentioning
confidence: 84%
“…Experiments have shown that the presence of Erwinia can affect negatively E.coli O157:H7 inoculum on lettuce leaves (32), and this is explained as competition for food, where better adapted species suppress competition. It was determined in previous experiments that Enterobacter adversely affect the adherence and colonization of Erwinia species in lettuce (31). However, some recent research have confirmed the opposite, as in the case of pectinovorum species, which makes lesions on the surfaces as additional sites for pathogenic microorganisms to adhere and penetrate their hosts more easily (40).…”
Section: Resultsmentioning
confidence: 95%